2017
DOI: 10.21320/2500-2139-2017-10-2-191-205
|View full text |Cite
|
Sign up to set email alerts
|

Chromothripsis in Oncology: Literature Review and Case Report

Abstract: The article presents a clinical case and literature review dwelling on the recently discovered chromothripsis phenomenon in oncology. Chromothripsis is a type of complex genome changes when a chromosome is first torn into dozens and even thousands of fragments, and then these fragments are bound in a random manner. Sometimes, several chromosomes are involved in the restructuring. As a result, genome mutant zones are formed which trigger malignancies and congenital diseases. In other words, the use of certain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 86 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…So in a recent study, it was found that chromothripsis was detected in 100% cases of malignant tumors of the peripheral nerve sheath, and in 71% cases of germ cell tumors [ 48 ]. Chromothripsis is regularly found in blood cancer, cancer of the central nervous system, in soft tissue tumors and carcinomas [ 49 , 50 ], in osteosarcoma and glioblastoma [ 8 , 51 , 52 , 53 , 54 , 55 ]. It was found that the incidence of chromothripsis in cancer is significantly higher in patients with hereditary genetic disorders associated with gene mutations in the cell cycle and DNA repair [ 56 , 57 ].…”
Section: Prevalence Of Chromothripsismentioning
confidence: 99%
“…So in a recent study, it was found that chromothripsis was detected in 100% cases of malignant tumors of the peripheral nerve sheath, and in 71% cases of germ cell tumors [ 48 ]. Chromothripsis is regularly found in blood cancer, cancer of the central nervous system, in soft tissue tumors and carcinomas [ 49 , 50 ], in osteosarcoma and glioblastoma [ 8 , 51 , 52 , 53 , 54 , 55 ]. It was found that the incidence of chromothripsis in cancer is significantly higher in patients with hereditary genetic disorders associated with gene mutations in the cell cycle and DNA repair [ 56 , 57 ].…”
Section: Prevalence Of Chromothripsismentioning
confidence: 99%